2018
DOI: 10.1186/s12941-018-0267-8
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated to prevalence and treatment of carbapenem-resistant Enterobacteriaceae infections: a seven years retrospective study in three tertiary care hospitals

Abstract: BackgroundThe increasing incidence of carbapenem-resistant Enterobacteriaceae (CRE), has resulted in a difficult problem in the current clinical anti-infective treatment. We performed a retrospective analysis of prevalence and treatment for CRE infections patients.MethodsThis study was conducted in three tertiary care hospitals from January 1, 2010 to December 30, 2016. Baseline data, treatment, and outcomes were collected in patients with ventilator-associated bacterial pneumonia (VABP), bacteremia, complicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
28
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 27 publications
(31 reference statements)
3
28
1
1
Order By: Relevance
“…2 b). Vasopressors requirement was significantly superior in the inappropriate EAMT group with a mean duration of 8 days [ 6 14 ] versus 5 days [ 2 8 ] in the appropriate EAMT group, p = 0.026. There were no differences in ventilator days and in ICU stays between appropriate versus inappropriate EAMT (15 ± 5.9 vs 18 ± 7 days, p = 0.5 and 22 ± 12 vs 29 ± 15 days, p = 0.37 respectively).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…2 b). Vasopressors requirement was significantly superior in the inappropriate EAMT group with a mean duration of 8 days [ 6 14 ] versus 5 days [ 2 8 ] in the appropriate EAMT group, p = 0.026. There were no differences in ventilator days and in ICU stays between appropriate versus inappropriate EAMT (15 ± 5.9 vs 18 ± 7 days, p = 0.5 and 22 ± 12 vs 29 ± 15 days, p = 0.37 respectively).…”
Section: Resultsmentioning
confidence: 99%
“…Vasopressors requirement was significantly superior in the inappropriate EAMT group with a mean duration of 8 days [ 6 14 ] versus 5 days [ 2 8 ] in the appropriate EAMT group, p = 0.026.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, the reported susceptibility to meropenem and imipenem among bla IMP-6 positive E. coli was approximately 70% and 100% (4). Pang et al have reported that most pathogens have been confirmed to produce IMP-type carbapenemases, and some cases have been successfully treated with quinolone monotherapy as a definitive therapy based on drug susceptibility tests (7). However, in the present study the isolates did not show resistance to levofloxacin, amikacin, and carbapenems based on the CLSI definition, and the MICs of some isolates turned to be high enough to be resistant to these drugs especially meropenem (the MIC for all isolates was ≥ 16 μg/mL) at 100-fold the standard inoculum size.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, fortunately, many of the bla IMP-6 positive CPEs are susceptible to levofloxacin and amikacin (6). Thus, based on the results of drug susceptibility tests, some infectious cases caused by IMP-type carbapenemase producing Enterobacteriaceae have been treated with quinolone monotherapy (7).…”
Section: Introductionmentioning
confidence: 99%